Developing 21st Century Education and Digital Literacy Skills through Intercultural City Stories Project - Adesti Komalasari (Pioneer: Journal of Language and Literature, 2021)
As a higher education institution that highlights the 21st education, Sampoerna University has encouraged the lecturers to do projects that give students opportunities to develop skills needed in Industry 4.0 so they can participate in global competition. Besides having the skills, the students must also have Intercultural Communicative Competence (ICC) to be able to participate in the competition and by knowing the importance of the skills and the competence, students of Sampoerna University participated in a collaborative project with students from Malmo University in Sweden. The project encouraged learners to develop their critical, creative and digital skills by collaboratively studying the city as text. The focus was on critical multiliteracy and the promotion of intercultural communicative competence through first-hand experiences of virtual exchange in cross-cultural groups. The objectives of this research are to find out how Intercultural City Stories project applies the elements of Intercultural Communicative Competence, to analyze how Intercultural Communicative Competence gives impacts for Cross Cultural Understanding, to observe how the digital outcome of multimodal narratives improves the understanding of Intercultural Communicative Competence and digital literacy and to identify the reasons why Intercultural Communicative Competence plays important roles in 21st century education and in literacy.